Assessment of Nutrition Screening Tools in Pediatric Oncology: A Systematic Review - Farlina, Mutia; Mansur, Arif Rohman; Sari, Ira Mulya; Herien, Yelly; Deswita; Neherta, Meri; Sukma, Nadila Permata (Basic and Applied Nursing Research Journal, 2024)
Introduction: The global prevalence of children with cancer continues to increase, reaching 186.6 per 1 million children aged 0-19 years. Children with cancer face challenges in fulfilling nutrition due to increased energy needs due to disease and treatment side effects. Nutritional assessment using nutrition screening tools is currently highly variable and varies across health institutions. This study aims to critically describe the assessment of nutritional screening tools in ensuring suitability and sensitivity as well as advantages and disadvantages in identifying the nutritional needs of children with cancer. Methods: PRISMA was used as a guide in preparing a systematic literature review based on inclusion criteria to determine research articles, search strategies, and research findings. Databases used in this study included Pubmed and Science Direct. Results: The use of appropriate nutrition screening tools is essential for assessing the nutritional status of pediatric patients with cancer. Appropriate nutrition screening tools have a positive impact on the nutritional fulfillment of children with cancer. There are five different nutrition screening tools in assessing the sensitivity of nutrition screening tools in children with cancer and their advantages and disadvantages. The sensitivity of the Screening Tool for Childhood Cancer (SCAN) and the Pediatric Yorkhill Malnutrition Score (PYMS) was highly accurate in correctly identifying children with cancer at risk of malnutrition. Conclusions: This finding is expected to be a recommendation for health workers in choosing the right nutrition screening tool to monitor the nutritional status of pediatric patients with cancer during treatment.